Catalytically active prokaryotic Argonautes employ phospholipase D family proteins to strengthen immunity against different genetic invaders - Cheng, Feiyue; Wu, Aici; Li, Zhihua; Xu, Jing; Cao, Xifeng; Yu, Haiying; Liu, Zhenquan; Wang, Rui; Han, Wenyuan; Xiang, Hua; Li, Ming (mLife, 2024)
Prokaryotic Argonautes (pAgos) provide bacteria and archaea with immunity against plasmids and viruses. Catalytically active pAgos utilize short oligonucleotides as guides to directly cleave foreign nucleic acids, while inactive pAgos lacking catalytic residues employ auxiliary effectors, such as nonspecific nucleases, to trigger abortive infection upon detection of foreign nucleic acids. Here, we report a unique group of catalytically active pAgo proteins that frequently associate with a phospholipase D (PLD) family protein. We demonstrate that this particular system employs the catalytic center of the associated PLD protein rather than that of pAgo to restrict plasmid DNA, while interestingly, its immunity against a single‐stranded DNA virus relies on the pAgo catalytic center and is enhanced by the PLD protein. We also find that this system selectively suppresses viral DNA propagation without inducing noticeable abortive infection outcomes. Moreover, the pAgo protein alone enhances gene editing, which is unexpectedly inhibited by the PLD protein. Our data highlight the ability of catalytically active pAgo proteins to employ auxiliary proteins to strengthen the targeted eradication of different genetic invaders and underline the trend of PLD nucleases to participate in host immunity. Impact statement Mesophilic prokaryotic Argonautes (pAgos) have the potential to be developed into genome editing tools. We report a mesophilic archaeal Ago that is catalytically active and utilizes an associated phospholipase D (PLD) family nuclease to restrict foreign DNA. The partnership with the PLD nuclease significantly enhances the pAgo‐based immunity against single‐stranded viruses and is essential for resisting double‐stranded plasmids. Furthermore, it shows that introducing only the pAgo protein into bacterial cells can enhance editing efficiency, suggesting its potential for genome editing applications.